2018
DOI: 10.1007/s00464-018-6178-0
|View full text |Cite
|
Sign up to set email alerts
|

The change in groin pain perception after transabdominal preperitoneal inguinal hernia repair with glue fixation: a prospective trial of a single surgeon’s experience

Abstract: BackgroundAlthough inguinal hernia is one of the most common conditions requiring surgical treatment, no reliable information is available on the quality of life of patients with inguinal hernias before surgery. Additionally, patients with intense inguinal pain prior to surgery are more susceptible to postoperative chronic pain. In such cases, less invasive laparoscopic techniques can be used, allowing atraumatic mesh fixation to reduce postoperative pain. The aim of the study was to determine, whether these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
2
16
0
2
Order By: Relevance
“…On the other hand, the surgical outcome in the study groups (P, U and UA) did not significantly differ with regard to incidence rate and intensity of chronic pain as assessed after 3, 6 and 12 months or pain decrease or regression a year after surgery. Thus, our results do not confirm the adverse effect of fixation on the risk of chronic pain, which is in accordance with results of similar studies and meta-analyses [6,[16][17][18][19][20]. On the other hand, the outcome of our study is contradictory to the study results of some other authors [9][10][11]21].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…On the other hand, the surgical outcome in the study groups (P, U and UA) did not significantly differ with regard to incidence rate and intensity of chronic pain as assessed after 3, 6 and 12 months or pain decrease or regression a year after surgery. Thus, our results do not confirm the adverse effect of fixation on the risk of chronic pain, which is in accordance with results of similar studies and meta-analyses [6,[16][17][18][19][20]. On the other hand, the outcome of our study is contradictory to the study results of some other authors [9][10][11]21].…”
Section: Discussionsupporting
confidence: 65%
“…tacks, may prove to be a disadvantageous factor that increases the risk of damage to anatomical structures and the occurrence of chronic pain. Thus, the use of atraumatic alternatives such as self-gripping meshes or fibrin glue may contribute to lower postoperative pain [3,[6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The other method for reducing postoperative pain in patients who have undergone laparoscopic inguinal hernia repair is fixation of mesh with glue [25,26]. A prospective trial that included 146 patients who underwent the laparoscopic TAPP method for inguinal hernia repair with fixation of mesh by glue showed that the frequency and intensity of the pain after surgery were significantly decreased compared to that experienced preoperatively, which is especially important for younger and professionally active patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, los pacientes refieren que el dolor mas alejado es en el cordón espermático, seguramente por la manipulación de la rama genital del nervio genitofemoral. Con el fin de disminuir aún más el dolor posoperatorio inmediato, seguimos utilizando un trocar de 10-12 mm a nivel umbilical y 2 trocares de 5 mm a nivel de flancos intentando una manipulación mínima del cordón espermático 27 . Al doler menos inicialmente, la fijación no invasiva también se relacionó con un menor requerimiento adicional de analgésicos y un retorno algo más precoz a las actividades habituales, ventajas que, sumadas a un menor número de complicaciones, hacen más recomendable su empleo.…”
Section: El Manejo Quirúrgico De Las Hernias Inguinales Cambió Debidounclassified
“…Los beneficios del uso de los pegamentos sintéticos en las herniorrafías inguinales por vía laparoscópica han sido publicados 22,[27][28][29][30] y nuestros resultados concuerdan con ellos, más aún cuando en el subgrupo de 57 pacientes con hernias inguinales bilaterales (un lado fue fijado con cianocrilato y el otro con fijadores) el dolor fue menor en el lado fijado con el pegamento.…”
Section: El Manejo Quirúrgico De Las Hernias Inguinales Cambió Debidounclassified